IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN PENCABULAN DI KOTA PAREPARE (Suatu Analisis terhadap Penerapan Undang-Undang No. 23 tahun 2002 tentang perlindungan anak) - Muh. Sudirman Sesse (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article outlines the implementation of the Legal Protection Against Child victims of abuse in Parepare normative juridical approach and empirical jurisdiction. Results reveal that cases of abuse against children in the City of Parepare in 2013, a decline of about 40 percent compared with the year 2012. It is seen that in 2012 there were 15 cases reported, while in 2013 there were 10 cases reported. The decline in abuse cases in the City of Parepare in 2013 due to several things, including; 1) increasing public awareness, 2) increasing awareness of religious communities, and 3) the cooperation between the security forces in the fight against social ills such as alcoholism, gambling, sexual abuse and so forth. Factors that may influence the occurrence of the crime of sexual abuse against minors in Pareare, namely: lack of education and economic factors, environmental factors or a place to stay, factors drinks (alcoholic), technological factors and factors etiologic role of victims in the domain of criminology can categorized on the theory of non-oriented social class. In addressing the crime of sexual abuse in the City of Parepare, Parepare district police have been enforcing the law properly. The fix is to patrol/regular raids and legal counseling to the community.